If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = (-4) + -2 y = -4 + -2 Combine like terms: -4 + -2 = -6 y = -6 Solving y = -6 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = -6
| (q-4)*4=32 | | -16t^2-17t+4=8 | | q=2-(-8) | | q-9=-7 | | (-7)+x=-15 | | 33-X=-2(1+3x) | | 18n^2+27n=0 | | -7(5b-8)+k=239 | | 5cos^2x+4cosx+1=0 | | 32=-4(k-6) | | 7-18=4y-3y+4 | | 3(5x-180+45)=-4(x-72) | | 52x(x-7)=43 | | -2(x+8)=36 | | g(2)+4g-32=0 | | 2-5x+6=14x-32+10(2-x) | | Y=-7/8-9/8 | | X/4-10=-4 | | 6m-13=47 | | (3y+2)+(2y+13)= | | 4x-7-36=0 | | 3m+(5+m)+5= | | 7(5+3r)=203 | | 4y-9=10 | | 4.25/0.75 | | 4x-7+6x=13-10 | | (x+4)(x+5)=1 | | x+10-15=0 | | 14+5x+2x=49 | | 2.840=1.2x-0.2x^2 | | -8y-7=9 | | 3(y+2)=2y+13 |